Prevalence of type 2 inflammation in patients with chronic rhinosinusitis with nasal polyps in Saudi Arabia - Aldajani, Ahmad; Alroqi, Ahmad; Alramyan, Rana; Alhejin, Nujud; Alswayyed, Mohammed; Alrajban, Waleed A.; Alromaih, Saud; Aloulah, Mohammad O.; Alrasheed, Abdulaziz S.; Aldousary, Surayie; Alsaleh, Saad (Frontiers in Surgery, 2024)
Background: Chronic Rhinosinusitis (CRS) is a common condition causing a significant worldwide burden, affecting 5-12% of the general population. CRS is classified into type 2 and non-type 2 disease based on endotype dominance. Type 2 inflammation is distinguished by the presence of IL-4, IL-5, and IL-13 cytokines, along with eosinophil and mast cell activation and recruitment. Evidence of type 2 inflammation is ascertained by tissue eosinophil count >10/high-power field (HPF) or serum eosinophil >250 cells/mcL or total immunoglobulin E (IgE) >100 IU/mL.